2011
DOI: 10.1002/pssc.201000283
|View full text |Cite
|
Sign up to set email alerts
|

Dopant diffusivity and solubility in nickel silicides

Abstract: Boron and Arsenic diffusion in implanted Ni2Si and NiSi layers has been studied using secondary ion mass spectrometry. These measurements show that As should not diffuse in the silicides at the temperatures used for silicidation. In contrast significant B diffusion is observed in both silicides at temperatures as low as 400°C. It is also observed that both dopants have higher solubilities in Ni2Si than in NiSi. B and As solubilities below 1.1020 at.cm‐3 are measured in NiSi (© 2011 WILEY‐VCH Verlag GmbH & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The higher SBH of DS-NiSi/n-Si was attributed to the electric dipoles introduced by the B DS at the NiSi/n-Si interface. , During the DS process, the B dopants were first implanted into the as-formed NiSi film. Upon subsequent drive-in annealing, because of the limited solubility of B in NiSi, soluble B dopants could not be incorporated into the NiSi film and would instead tend to diffuse out of the NiSi film and finally accumulate at the NiSi/n-Si interface, where the B dopants partially substituted for the Si atoms on the Si lattice in close vicinity to the NiSi/n-Si interface. , Secondary ion-mass spectroscopy (SIMS) analysis was performed to profile the depth distribution of boron dopants in NiSi/n-Si after DS. As shown in Figure , the boron dopants accumulated at the NiSi/n-Si interface after DS.…”
Section: Resultsmentioning
confidence: 99%
“…The higher SBH of DS-NiSi/n-Si was attributed to the electric dipoles introduced by the B DS at the NiSi/n-Si interface. , During the DS process, the B dopants were first implanted into the as-formed NiSi film. Upon subsequent drive-in annealing, because of the limited solubility of B in NiSi, soluble B dopants could not be incorporated into the NiSi film and would instead tend to diffuse out of the NiSi film and finally accumulate at the NiSi/n-Si interface, where the B dopants partially substituted for the Si atoms on the Si lattice in close vicinity to the NiSi/n-Si interface. , Secondary ion-mass spectroscopy (SIMS) analysis was performed to profile the depth distribution of boron dopants in NiSi/n-Si after DS. As shown in Figure , the boron dopants accumulated at the NiSi/n-Si interface after DS.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that both As and B dopants have higher solubilities in Ni 2 Si than in NiSi. 41 During the drive-in anneals in the modified scheme, the soluble As or B dopants in Ni 2 Si have to be expelled out and pile up at the NiSi/Si interface. These two factors lead to the more pronounced As and B DS at the NiSi/Si interface in the modified scheme.…”
Section: Resultsmentioning
confidence: 99%